Global Experiences from Regulatory Sandboxes - World Bank (World Bank, Washington, DC, 2020)
Regulatory sandboxes have become synonymous with fintech innovation and offer the unique benefit of providing the empirical evidence needed to substantiate decisions. This paper on Global Experiences from Regulatory Sandboxes brings together detailed lessons learned and case studies from sandboxes across the globe. Our research has identified 73 sandboxes in 57 jurisdictions. This is currently the most up-to-date resource for sandboxes available and is supplemented with an interactive database on Key data from Regulatory Sandboxes across the globe.